Methodology and Experimental Investigation of Linear Creep Behavior in Two-Layer Reinforced Concrete Beams - Iakov Iskhakov; Klaus Holschemacher; Stefan Kaeseberg; Yuri Ribakov (Applied Sciences)
This paper presents the first stage of an experimental investigation of creep in two-layer reinforced concrete beams. It deals with the methodology of testing beams under long-term loading aimed at the investigation of the real linear creep effect. The investigated beams consisted of a normal-strength concrete (NSC) in the tensile zone and steel-fibered high-strength concrete (SFHSC) in the compression one. The specimens are subjected to four-point bending under loads that correspond to 70 and 85% of their load-bearing capacity. The loads are applied using special amplifying devices. The experiments at this stage lasted 90 days. Deflections are measured in the midspan of each specimen. During the first 24 h after applying the loads, the deflections were recorded every 10 s, and after 24 h, every hour. During the tests, no cracks have been observed near the supports as well as between the NSC and SFHSC layers. The cracks appeared within the limits of the pure bending zone only. Load-deflection curves were obtained and analyzed. The maximum midspan deflection in the tested beams was less than 1/250 of the beam span, which indicated that at linear creep, the two-layer beams are safe and remain in the elastic stage. The obtained results form a basis for the second stage of the experimental research that will be focused on the non-linear creep effect in such beams.